2023
DOI: 10.3390/ma16031170
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies into Cutting of a Novel Two Component 3D-Printed Stainless Steel–Polymer Composite Material by Abrasive Water Jet

Abstract: Composites are materials with a heterogeneous structure, composed of two or more components with different properties. The properties of composites are never the sum or average of the properties of their components. There is a lot of research and many models on the different property assessments of composite materials. Composites are used as construction materials in key areas of technology, including in civil and mechanical engineering, aviation and space technology, and others. This work presents a modern co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Moreover, they demonstrate that the parameter standoff distance is the most significant factor affecting the machining result. Tomasz Szatkiewicz and his colleagues applied AWJM on 3-D printed stainless steel-polymer composite and predicted the most influencing parameter on surface roughness through the S-N ratio [14]. Andrzej Perec et al worked on AWJM of industrial phenolic composite and developed a cutting model through a second-degree multinomial equation.…”
Section: Of 14mentioning
confidence: 99%
“…Moreover, they demonstrate that the parameter standoff distance is the most significant factor affecting the machining result. Tomasz Szatkiewicz and his colleagues applied AWJM on 3-D printed stainless steel-polymer composite and predicted the most influencing parameter on surface roughness through the S-N ratio [14]. Andrzej Perec et al worked on AWJM of industrial phenolic composite and developed a cutting model through a second-degree multinomial equation.…”
Section: Of 14mentioning
confidence: 99%
“…Sharma et al [ 71 ] found a significant effect of travel speed on surface roughness and kerf angle taper in cutting H13 die steel, as did Hascalik et al [ 72 ] in cutting Ti6Al4V alloy. Szatkiewicz et al [ 73 ] investigated the effect of process parameters of abrasive water jets on the cutting of stainless steel–polymer composite material. It was found that traverse speed was the most significant factor influencing roughness, followed by pressure and abrasive flow rate.…”
Section: Influencing Factors In the Processing Removal Process Of Abr...mentioning
confidence: 99%